Differences in the plasma phospholipid profile of patients infected with tick-borne encephalitis virus and co-infected with bacteria - Groth, Monika; Łuczaj, Wojciech; Dunaj-Małyszko, Justyna; Skrzydlewska, Elżbieta; Moniuszko-Malinowska, Anna (Scientific reports, 2022)
Tick-borne encephalitis (TBE) is an infectious viral disease, the pathogenesis of which is still not fully understood. Additionally, TBE can be complicated by co-infections with various bacteria that are also transmitted by ticks, which can affect the proper diagnosis and treatment. Therefore, the aim of the study was to evaluate changes in the plasma phospholipid (PL) and ceramide (CER) profile of patients with TBE and patients with bacterial co-infection ( B. burgdorferi or A. phagocytophilum ) in relation to healthy subjects. For this purpose, a high-resolution LC-QTOF-MS/MS platform as well as univariate and multivariate statistics were used. The results of this study showed that the levels of phosphatidylcholines (PC) and lysophosphatidylcholines (LPC) species were increased in the plasma of patients with TBE and patients with TBE co-infected with bacteria. On the other hand, observed differences in the content of phosphoethanolamines (PE) and sphingomyelins (SM) make it possible to distinguish TBE patients from patients with co-infections. The opposite direction of changes was also observed in the CER content. This study showed significant modifications to the metabolic pathways of linoleic (LA) and arachidonic acid (AA), as confirmed by the quantitative analysis of these fatty acids. The obtained results allow to distinguish the pathomechanism of TBE from TBE with bacterial co-infection, and consequently may improve the diagnostic process and enable more efficient pharmacotherapy against both pathogens.